Impact of Parental Monitoring on Risk Behaviors: The Mediating Role of Moral Identity - Tanaka, Daiki; Chen, Liang; Santoso, Agus (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the relationship between parental monitoring and adolescent risk behaviors, examining the mediating role of moral identity in this association.Methods and Materials: A descriptive correlational design was used with a sample of 414 high school students from China, selected based on the Krejcie and Morgan sample size determination table. Data were collected using three standardized instruments: the Parental Monitoring Scale (Stattin & Kerr, 2000), the Moral Identity Questionnaire (Aquino & Reed, 2002), and the Risk Involvement and Perception Scale (Benthin et al., 1993). Descriptive statistics and Pearson correlation coefficients were calculated using SPSS-27 to assess bivariate relationships, and Structural Equation Modeling (SEM) was conducted with AMOS-21 to evaluate direct, indirect, and total effects among the variables and test model fit indices.Findings: Descriptive results indicated moderate levels of parental monitoring (M = 35.62, SD = 5.13), moral identity (M = 38.47, SD = 6.29), and relatively low levels of risk behaviors (M = 24.18, SD = 7.64). Pearson correlations revealed significant associations: parental monitoring positively correlated with moral identity (r = .42, p < .001) and negatively with risk behaviors (r = –.51, p < .001); moral identity was also negatively associated with risk behaviors (r = –.47, p < .001). SEM results confirmed that moral identity partially mediated the relationship between parental monitoring and risk behaviors, with a good model fit (χ²/df = 1.97, CFI = 0.96, RMSEA = 0.048). The total effect of parental monitoring on risk behaviors was significant (β = –0.57, p < .001), including both direct (β = –0.43) and indirect effects through moral identity (β = –0.14).Conclusion: Parental monitoring significantly reduces adolescent risk behaviors both directly and indirectly through the development of moral identity, highlighting the importance of fostering both external regulation and internal value systems in youth.